1998
DOI: 10.1063/1.366556
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of scanning tunneling microscopy tips under laser illumination

Abstract: The periodic thermal expansion of scanning tunneling microscopy (STM) tips arising under irradiation with power-modulated laser light has been investigated. The expansion was determined by comparison with a calibrated piezomotion measured in an STM, which was operated in the constant-current mode, and instrumental effects were corrected for. The experimental data concerning the frequency response of the thermal expansion for various geometries of the tip and for different positions of the laser focus are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 21 publications
4
58
0
1
Order By: Relevance
“…From these observations we shall draw the important conclusion that thermal expansion alone cannot explain the LIS. In similar experiments but using an STM instead of a MCB, it has been shown that thermal expansion is the most important mechanism giving rise to conductance changes 4,11 .…”
Section: Because Of the Individual Rearrangements It Is Difficult To mentioning
confidence: 99%
See 1 more Smart Citation
“…From these observations we shall draw the important conclusion that thermal expansion alone cannot explain the LIS. In similar experiments but using an STM instead of a MCB, it has been shown that thermal expansion is the most important mechanism giving rise to conductance changes 4,11 .…”
Section: Because Of the Individual Rearrangements It Is Difficult To mentioning
confidence: 99%
“…One rather trivial effect is the geometry change of the tips due to thermal expansion because of the deposited energy of the laser pulse. This effect has been shown to be the dominating one for a scanning tunneling microscope (STM) under pulsed laser light irradiation 4,11 . However, for the MCB geometry this effect is expected to be much smaller due to the very small dimensions of the freestanding bridge arms.…”
mentioning
confidence: 99%
“…Clusters ofstructures of the top layers. Individual Pt atoms are clearly identified, especially for (c) Pt (8) and (d) Pt (9), indicating that the geometry of the clusters is atomically resolved and the details can be analyzed with a CNT tip. …”
Section: (A) Mechanical Attachment Methodsmentioning
confidence: 99%
“…The first is the spurious spectra that are often generated by temporal instabilities or positional drift of the STM tip, which cause the tunneling current to change with time because acquisition for LI detection requires a long time to sweep the wavelength of spectroscopic light. The second problem is an undesirable excess component in the photomodulated tip current due to the photothermal expansion of the tip material [8].…”
Section: Fourier Transform Stm-pasmentioning
confidence: 99%
“…Thermal effects can impact the measurement in a number of ways, for example probe elongation or shortening [26,[28][29][30][31][32][33][34], widening of the probe aperture [31], expansion of a metal coating past the dielectric core of the probe [32], changes in the metal work function and thus the capacitance present between the tip and sample [35], and of course in extreme cases thermally induced damage [36].…”
Section: Indirect Effects Of Optical Fieldsmentioning
confidence: 99%